2020
DOI: 10.1186/s12889-020-8417-2
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of continuity of HIV care following release from correctional facilities in South Africa

Abstract: Background: We sought to describe linkage to care, ART continuity, and factors associated with linkage to care among people with HIV following release from incarceration in South Africa. Methods: We conducted a study of South African correctional service community reentrants who were receiving ART at the time of release. The study was implemented in three of 46 correctional service management areas. Participants were enrolled prior to corrections release and followed up to 90 days post-release to obtain selfre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…The TCAC was tailored to overcome care transition challenges particularly affecting HIV-positive re-entrants. It was informed by a model of key barriers to care transition developed from prior work and the Behavioral Model for Vulnerable Populations [12,17,34]. The intervention was specifically designed to improve retention in HIV care and ART adherence among re-entrants by addressing logistical barriers to care, long wait times at clinics, clinic-based enacted stigma toward HIV and incarceration, low social support, substance use, and joblessness.…”
Section: Program Description: Transition Community Adherence Clubmentioning
confidence: 99%
See 1 more Smart Citation
“…The TCAC was tailored to overcome care transition challenges particularly affecting HIV-positive re-entrants. It was informed by a model of key barriers to care transition developed from prior work and the Behavioral Model for Vulnerable Populations [12,17,34]. The intervention was specifically designed to improve retention in HIV care and ART adherence among re-entrants by addressing logistical barriers to care, long wait times at clinics, clinic-based enacted stigma toward HIV and incarceration, low social support, substance use, and joblessness.…”
Section: Program Description: Transition Community Adherence Clubmentioning
confidence: 99%
“…However, many face care transition challenges upon release, which leads to low engagement in HIV care and poor ART adherence during re-entry [8][9][10][11]. A study among 351 HIV-positive re-entrants in South Africa found that only 34% of participants had no lapse in ART supply within 90 days of release [12]. A meta-analysis of linkage to care studies from the United States (U.S.) reported similar proportions of post-release linkage to care with a median of 36% [13].…”
Section: Introductionmentioning
confidence: 99%
“…7 Strategies to promote continued engagement in care for incarcerated individuals following their release from correctional facilities are required to ensure sustainability of efforts. 8 The ongoing COVID-19 pandemic and subsequent development of effective vaccines have demonstrated what can be done when there is a collective political will and resources are made avail able. These aspects still remain key barriers for tuberculosis and HIV control in correctional facilities.…”
Section: Tuberculosis In Prisons: An Unintended Sentence?mentioning
confidence: 99%
“…Unfortunately, such benefits are short‐lived for PLHIV after release (“releasees”) due to problems with post‐release care continuity posed by multiple psychosocial, health system and structural barriers [ 6 , 12 , 13 , 14 , 15 ]. Although data to quantify the extent of the problem in SSA are scarce, available reports suggest that one‐third or more of releasees fail to link to community care or experience HIV treatment interruption post‐release [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, such benefits are short-lived for PLHIV after release ("releasees") due to problems with post-release care continuity posed by multiple psychosocial, health system and structural barriers [6,[12][13][14][15]. Although data to quantify the extent of the problem in SSA are scarce, available reports suggest that one-third or more of releasees fail to link to community care or experience HIV treatment interruption post-release [16,17]. Despite these HIV care disruptions, no studies from SSA have attempted to assess HIV service delivery preferences among incarcerated PLHIV as they transition from prisons into the community, and specific recommendations about interventions to promote post-release HIV care continuity are lacking [18,19].…”
Section: Introductionmentioning
confidence: 99%